The interspecies educator's cybernetic world. Issue 1 (28th January 2014) - Affifi, Ramsey
Abstract : Purpose: – The purpose of this paper is to interconnect pedagogy and biology via second-order cybernetics. Design/methodology/approach: – The approach taken is that of a synthesis. Findings: – Biology can better deal with intersubjectivity within and between species by incorporating approaches and theory from education inquiry. Conversely, educators can de-anthropocentrize their discipline by entering into learning relationships with other species. By rallying around the concept of "eduction", second-order cybernetics plays a role in both syntheses. Practical implications: – De-anthropocentrizing education could have practical value in creating ecologically relevant education for children and in developing more integrated environmental impact assessments. Originality/value: – Finding convergence between the study of life and forms of practitioner inquiry in education research, and connecting these to the environmental movement.